Extended biofilm formation time by Streptococcus sanguinis modifies its non-cariogenic behavior, in vitro - Natalia DÍAZ-GARRIDO; Carla Paola LOZANO; Jens KRETH; Rodrigo Andrés GIACAMAN (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract Although the commensal Streptococcus sanguinis [ S. sanguinis] is isolated from caries-free people, it can ferment carbohydrates producing acids. We aimed to characterize S. sanguinis cariogenic potential as a function of different enamel biofilm formation periods, in vitro. Saliva-coated enamel slabs were inoculated with S. sanguinis to form initial biofilms for 8, 12 or 16 h in presence of sucrose and followed by a period in medium with glucose for 16, 12 or 8 h, respectively, until completion of 24 h. To simulate cariogenic challenges, S. sanguinis biofilms were exposed to 10% sucrose for 5 minutes, 3x/day for 5 days. Biofilm biomass, viable cells, total proteins, intracellular and extracellular polysaccharides production, acidogenicity and enamel demineralization were determined. Biofilms of Streptococcus mutans [ S. mutans ] served as caries-positive control. Biofilms of S. sanguinis forming on enamel for 12 and 16 h showed higher demineralization than those formed during 8 h, but lower than S. mutans biofilms, regardless of the initial biofilm formation time. No differences were detected in the biofilm properties among the different biofilm formation times tested for S. sanguinis . Increased enamel initial biofilm formation time by S. sanguinis appears to induce a cariogenic potential, but lower than S. mutans .